2020
DOI: 10.3390/ma13153330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Placement Technology on the Bond Strength Between Two Layers of Self-Compacting Concrete

Abstract: Self-compacting concrete (SCC) should generally be placed continuously, but it is not uncommon for contractors to be forced to use interruptions in concrete works due to delivery delays. The multilayer casting of SCC can cause weak bond conditions in the contact area of subsequent layers. Methods of preventing cold joint or lift line formation for normal concretes are not suitable for self-compacting concretes. This article provides research on the effect of multilayer casting technology on the bond strength b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In the technological variant where the previously laid layer was mechanically disturbed, no average decrease occurred for a delay of 15 minutes, while for delays of 30 and 60 minutes, it was 6.0% and 11.4%, respectively. Similar results were observed in experiments conducted on beam elements (14). Additionally, studies employing mixes with different thixotropy ratios (16,17) reported that for a delay of 60 minutes, the residual strength of the joint ranged from 56% to 91% -for the inclined shear test, 15% to 76% -for the direct shear test, and 56% to 80% -for the flexural strength test.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the technological variant where the previously laid layer was mechanically disturbed, no average decrease occurred for a delay of 15 minutes, while for delays of 30 and 60 minutes, it was 6.0% and 11.4%, respectively. Similar results were observed in experiments conducted on beam elements (14). Additionally, studies employing mixes with different thixotropy ratios (16,17) reported that for a delay of 60 minutes, the residual strength of the joint ranged from 56% to 91% -for the inclined shear test, 15% to 76% -for the direct shear test, and 56% to 80% -for the flexural strength test.…”
Section: Introductionsupporting
confidence: 79%
“…Additionally, it was found that applying a second layer with a thickness significantly exceeding that recommended [100 mm] (15) was not adequate to achieve a shear effect between the two layers during a delay time of 60 minutes. Considering both the outcomes of this research and findings in the literature (13,14,16,17), the recommendation is to place successive layers of SCC mix in beam and wall elements with a thickness of ≥100 mm, allowing a delay of up to 30 minutes.…”
Section: Recommendationsmentioning
confidence: 99%
“…The authors drew analogous conclusions in their previous publication based on self-compacting concrete with a binder content of 450 kg/m 3 [ 16 ]. That mixture exhibited stronger thixotropic behaviour and the variant of casting the mixture onto an undisturbed surface resulted in greater deterioration of the load-bearing capacity of the joint between successive layers.…”
Section: Discussionmentioning
confidence: 59%
“…A considerable number of studies with new generation concretes [ 3 , 5 , 16 , 17 ] were conducted on the load-bearing capacity of the joint resulting from delays using different destructive tests. A reduction in mechanical strength of more than 40% was reported on the cylindrical core samples using a simple compression test [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation